MicroRNAs, endometrial receptivity and molecular pathways - Soheila Salmasi; Mohammad Saeed Heidar; Mahmood Khaksary Mahabady; Bahman Rashidi; Hamed Mirzaei (BMC, 2024)
Abstract MicroRNAs (miRNAs) are a type of specific molecules that control the activities of the uterus, such as the process of cellular maturing and evolution. A lot of substances like growth factors, cytokines, and transcription factors play a role in embryo-endometrial interaction. MiRNAs could regulate various these factors by attaching to the 3' UTR of their mRNAs. Moreover, current research show that miRNAs participate in formation of blood vessels in endometrium (miR-206, miR-17-5p, miR-16-5p...), decidualization (miR-154, miR-181, miR-9...), epithelial-mesenchymal transition (miR-30a-3p), immune response (miR-888, miR-376a, miR-300...) embryo attachment (miR-145, miR-27a,451...) and pinopod formation (mir-223-3p, mir-449a, mir-200c). In this study, the focus is on the role of miRNAs in managing the uterus' receptivity to an embryo and its ability to facilitate attachment. More specifically, we are exploring the mechanisms by which miRNAs regulate the presence of specific molecules involved in this crucial physiological process.